’To be tensed or not to be tensed?’ The case of Vietnamese - Phan, Trang; Duffield, Nigel (Investigationes Linguisticae, 2019)
In this paper, we scrutinise the interpretation and distribution of a number of morphemes that serve as means of expressing temporal/aspectual relations in Vietnamese, investigating whether they should treated as genuine tense and aspect markers. The main goals of the study are two-fold: (i) empirically, to offer a comprehensive description of Vietnamese tense and aspect, in both pre-verbal and post-verbal domains; (ii) theoretically, to offer new pieces of evidence supporting the claim that Tense and Aspect exist as independent functional categories in Vietnamese.